The Mediating Effects of Generational Affiliation to The Influence of Principals’ Digital Leadership on Teachers’ Technological Self-Efficacy - Paunil, Lawrence Oliver V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
New technology developments are rapidly altering the teaching and learning environment. Schools require leaders who can assist the transformation process and promote a digital culture of learning. As a result, this study aims to determine the influence of the respondents’ perceived digital leadership of principals on their technological self-efficacy when mediated by generational affiliation among private schools in Quezon province. Two instruments were used in this study: The principals’ Digital Leadership questionnaire, which is based on the International Society for Technology Education (ISTE) standard for Education Leaders (2022) was administered to school principals/heads, while Teachers’ Technological Self-Efficacy Questionnaire, which is based on the ISTE standard for Educators (2022) was administered to teachers. Descriptive and Inferential analysis was carried out using SPSS. The findings showed that the respondents significantly demonstrated generational work-related orientation, digital leadership, and technological self-efficacy. Furthermore, when respondents were categorized by generational affiliation, there were no significant differences in their work-related orientation, digital leadership, and technological self-efficacy. On the other hand, there was a significant influence of the principals’ digital leadership on teachers’ technological self-efficacy. Moreover, the respondents' generational affiliation/work-related orientation mediates the direct influence of Principals’ Digital Leadership on the Teachers’ Technological Self-efficacy. Principal preparation programs and teacher training programs may include technology-based leadership to improve technology integration in classrooms. It is advised that further studies be conducted on digital leadership and technical self-efficacy for administrators and teachers.